2021
DOI: 10.3390/su13168690
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Change of Land Use in a Coastal Reclamation Area: A Complex Network Approach

Abstract: Coastal ecological protection and restoration projects aimed to restore and recover the ecological environment of coastal wetland with high-intensity human reclamation activity, while the integrity of the coastal wetland system with human reclamation activity and the ability of individual land use types to control the overall system were not fully considered. In this study, a six-stage land use conversion network was constructed by using a complex network model to analyze coastal land use dynamic changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To make the land structures of different development stages more comparable, the equilibrium degree of land use structure (E) is introduced as a quantity reflecting the equilibrium of land use structure. E ∈ [0, 1], and the larger the value of equilibrium degree, the stronger the equilibrium [38,39].…”
Section: Information Entropy and Equilibrium Degree Of Land Use Struc...mentioning
confidence: 99%
“…To make the land structures of different development stages more comparable, the equilibrium degree of land use structure (E) is introduced as a quantity reflecting the equilibrium of land use structure. E ∈ [0, 1], and the larger the value of equilibrium degree, the stronger the equilibrium [38,39].…”
Section: Information Entropy and Equilibrium Degree Of Land Use Struc...mentioning
confidence: 99%
“…Figure 1. The land use and cover change of the study area has been analyzed, which can be seen from Xu et al (2021) [18]. In a nutshell, the land-use types of the study area with the effect of reclamation activity in the past decades had gradually transformed from being dominated by natural types (e.g., tidal flat, halophytic vegetation) to artificial types (e.g., cropland, aquaculture pond, and construction land).…”
Section: Study Areamentioning
confidence: 99%
“…Specifically, the dynamic conditions of the tidal flat, the elevation gradient, and the soil salinity determine the distribution and composition of the plant community [22,54,55]. Moreover, human activities resulting in different land-use types and soil physical and chemical properties are important factors affecting the growth and succession of vegetation in coastal reclamation areas [18,52,56]. Further analysis should focus on the impact of environmental factors on plant community characteristics and species diversity, and an in-depth analysis of the coupling relationship between human activities, environmental factors, and plant community characteristics, and reveal the effect of reclamation activities on the coastal wetland ecosystems.…”
Section: The Succession Process Of Plant Community With Coastal Recla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Krom 2012 conducted a laboratory study of rubble mound breakwaters with nondeformable rock armor parts and investigated the effect of porosity on the rate of overtopping and showed that porosity has a great effect on the rate of overtopping. The results also showed that in porous structures, the experimental formulas used to predict overtopping are not able to correctly predict overtopping [12][13][14]. Mousavi et al, 2017 conducted tests on the physical model of the breakwater with antifer block armor against the weight loss of the blocks, and with a 10% reduction in the weight of the block, the severity of the damage intensified.…”
Section: Introductionmentioning
confidence: 99%